## Find the inverse of the function

To find the inverse of the function (f(x) = (x - 1) / (x + 1)), we need to interchange x and y, then solve for y. Then, the inverse function is y = (x+1)/(x-1).

<p>To find the inverse of the function f(x) = (x - 1) / (x + 1), we will switch x and y and then solve for y.</p><p>x = (y - 1) / (y + 1)</p><p>Multiplying both sides by y + 1, we get:</p><p>x(y + 1) = y - 1</p><p>Expanding the left side and simplifying, we get:</p><p>xy + x = y - 1</p><p>Subtracting xy from both sides, we get:</p><p>x - xy = y - 1</p><p>Factoring out y on the right side, we get:</p><p>x - xy = y(1 - x)</p><p>Dividing both sides by 1 - x, we get:</p><p>y = (x - 1) / (1 - x)</p><p>Therefore, the inverse of the function f(x) = (x - 1) / (x + 1) is:</p><p>f^-1(x) = (x - 1) / (1 - x)</p>

Post your answer

Sign in to post your amazing answer.